The Association between Self Esteem and Self-Efficacy With Mental Illness in Pregnant Women - Adang Bachtiar; Cicilya Candi; Nurul Husnul Lail (Journal of Health Promotion and Behavior, 2019)
Background: A study in Indonesia conducted in the DKI Jakarta area in 2002 showed that 15% experienced depression during pregnancy and 20% depression after childbirth. Self esteem and self efficacy are things that affect mental condition. This study aims to determine the relationship of self-esteem and self-efficacy on health conditions in pregnant women.Subjects and Method:This study is a quantitative study with cross-sectional design involving a sample of 182 respondents from midwife independent practice in East Jakarta in January-June 2019. Univariate analysis was used to determine the description of the characteristics of respondents. SEM analysis was used to determine the relationship between variables of self-esteem, self-efficacy and mental health.Results:The interaction of self esteem and self efficacy shows a strong relationship of 0.9. The path coefficient from self esteem to mental health of -0.55, from self efficacy to mental health of -0.04.Conclusion:Self esteem for mental illness has a negative effect with a moderate effect. Self efficacy also has a negative direction and is very weak.Keywords: mental health, maternal mental health, postpartum blues/depressionCoresspondence: Cicilya Candi. Faculty of Public Health, Universitas Indonesia, Depok, West Java, Indonesia. Email: cicilya.ui2014@gmail.com.Journal of Health Promotion and Behavior (2019), 4(4): 267-273https://doi.org/10.26911/thejhpb.2019.04.04.03